Complex Eigenvalue Analysis of A Motorcycle Disc Brake Squeal - Zahrul Fuadi; Muhammad Nizar Machmud (Jurnal Teknik Mesin Unsyiah, 2012)
This paper discusses the phenomenon of brake squeal of a disc brake system used at motorcycle with a capacity of 125 cc. The occurrence of disc brake squeal is associated with the dynamic instability of the system with the influence coefficient of friction. The dynamic instability of the system is predicted using finite element complex eigenvalue analysis. The analysis predicted three unstable modes in the frequency range below 5 kHz. The unstable modes occurred at the frequency of 1250 Hz, 1920 Hz, and 2306 Hz. The occurrence of unstable mode is indicated by the presence of positive real part of the corresponding complex eigenvalue. Unstable mode is shown by the occurrence of coupled vibration between eigenvectors of disc and brake pads vibrating at similar frequency which consists of diametral mode of disc and bending modes of pads. The analysis also showed that the unstable condition could occur at a value of coefficient of friction as low as 0.2.